The hypoxia-inducible factor 1 pathway plays a critical role in the development of breast muscle myopathies in broiler chickens: a comprehensive review - Alnahhas, Nabeel; Pouliot, Eric; Saucier, Linda (Frontiers in Physiology, 2023)
In light of the increased worldwide demand for poultry meat, genetic selection efforts have intensified to produce broiler strains that grow at a higher rate, have greater breast meat yield (BMY), and convert feed to meat more efficiently. The increased selection pressure for these traits, BMY in particular, has produced multiple breast meat quality defects collectively known as breast muscle myopathies (BMM). Hypoxia has been proposed as one of the major mechanisms triggering the onset and occurrence of these myopathies. In this review, the relevant literature on the causes and consequences of hypoxia in broiler breast muscles is reviewed and discussed, with a special focus on the hypoxia-inducible factor 1 (HIF-1) pathway. Muscle fiber hypertrophy induced by selective breeding for greater BMY reduces the space available in the perimysium and endomysium for blood vessels and capillaries. The hypoxic state that results from the lack of circulation in muscle tissue activates the HIF-1 pathway. This pathway alters energy metabolism by promoting anaerobic glycolysis, suppressing the tricarboxylic acid cycle and damaging mitochondrial function. These changes lead to oxidative stress that further exacerbate the progression of BMM. In addition, activating the HIF-1 pathway promotes fatty acid synthesis, lipogenesis, and lipid accumulation in myopathic muscle tissue, and interacts with profibrotic growth factors leading to increased deposition of matrix proteins in muscle tissue. By promoting lipidosis and fibrosis, the HIF-1 pathway contributes to the development of the distinctive phenotypes of BMM, including white striations in white striping–affected muscles and the increased hardness of wooden breast–affected muscles.